Conduction of a chemical structure-guided metabolic phenotype analysis method targeting phenylpropane pathway via LC-MS: Ginkgo biloba and soybean as examples. (1st October 2022) - Meng, Jie; Zhang, Yiran; Wang, Guolin; Ji, Meijing; Wang, Bo; He, Guo; Wang, Qianwen; Bai, Fali; Xu, Kun; Yuan, Dongliang; Li, Shuai; Cheng, Yue; et al.
Graphical abstract: The workflow of this new strategy for the metabolic phenotype analysis of PPP. A. the biosynthesis relationship of PPP was summarized via the chemical structures of involved metabolites. B. the 103 key metabolites that reflect the metabolic phenotype of PPP were chosen to construct a structural periodic table according to their biosynthesis relationship. C. the characteristics of metabolic phenotype targeting PPP were elucidated according to the heatmap of metabolites filled in the structural periodic table. Highlights: A method template for high resolution of metabolic phenotype analysis targeting PPP was conducted based on accurate qualification and quantification of 103 structural associated metabolites via liquid chromatography tandem mass spectrometry. The delicate spatial-temporal metabolic balance of PPP from ginkgo biloba can be elucidated via this method. It is first confirmed that the salt and draught stresses could redirect the biosynthesis trend of PPP in soybean leaves to produce more isoflavones through this method. Abstract: The phenylpropane pathway (PPP) is one of the most extensively investigated metabolic routes. This pathway biosynthesizes many important active ingredients such as phenylpropanoids and flavonoids that affect the flavor, taste and nutrients of food. How to elucidate the metabolic phenotype of PPP is fundamental in food research and development. In this study, we designed a structural periodical table filled with 103 metabolites produced from PPP. All of them especially the 62 structural isomers were qualified and quantified with high resolution and sensitivity via multiple reaction mode in liquid chromatography tandem triple quadrupole mass spectrometry. Ginkgo biloba and soybean were used as samples for the practical application of this method: The delicate spatial-temporal metabolic balance of PPP from ginkgo biloba has been first elucidated; It is first confirmed that the salt and draught stresses could redirect the biosynthesis trend of PPP to produce more isoflavones in soybean leaves.